Belgian Views on Security Issues. - United States Information Agency. Office of Research.; Adler, Kenneth P. (Tufts University. Tisch Library., 2019)
This memorandum reports preliminary results of a USIA-sponsored study of West European public opinion on security issues. Personal interviews were conducted May 15-29 by DIMARSO, the Belgian Gallup affiliate, with a representative national sample of 1018 Belgian adults.; Research Memorandum M-7/25/84